2016
DOI: 10.1007/s10875-016-0359-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Type I Interferon Signaling in Pediatric Inflammatory Disease

Abstract: PurposeIncreased type I interferon is considered relevant to the pathology of a number of monogenic and complex disorders spanning pediatric rheumatology, neurology, and dermatology. However, no test exists in routine clinical practice to identify enhanced interferon signaling, thus limiting the ability to diagnose and monitor treatment of these diseases. Here, we set out to investigate the use of an assay measuring the expression of a panel of interferon-stimulated genes (ISGs) in children affected by a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
141
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 45 publications
(43 reference statements)
7
141
0
2
Order By: Relevance
“…In our study, galectin‐9 was a specific biomarker for inflammatory myopathies. In patients with juvenile DM, high circulating interferon‐α levels have been found, and in one group of patients with juvenile DM, more than 75% of patients had a positive interferon signature . Circulating galectin‐9 and CXCL10 levels could therefore be a direct reflection of active, interferon‐driven inflammation, which is supported by a recent study in which galectin‐9 was demonstrated to be a marker for the interferon signature in SLE and antiphospholipid syndrome .…”
Section: Discussionmentioning
confidence: 66%
“…In our study, galectin‐9 was a specific biomarker for inflammatory myopathies. In patients with juvenile DM, high circulating interferon‐α levels have been found, and in one group of patients with juvenile DM, more than 75% of patients had a positive interferon signature . Circulating galectin‐9 and CXCL10 levels could therefore be a direct reflection of active, interferon‐driven inflammation, which is supported by a recent study in which galectin‐9 was demonstrated to be a marker for the interferon signature in SLE and antiphospholipid syndrome .…”
Section: Discussionmentioning
confidence: 66%
“…20,21 We emphasize that the interferon signature remains elevated many years after disease onset, providing evidence of ongoing pathology. ADAR1 is expressed throughout the brain including the basal ganglia (http://www.brain-map.org), and it has been shown that a loss of ADAR1 renders cells more susceptible to apoptosis following stress, including infection.…”
Section: Discussionmentioning
confidence: 94%
“…Overexpression of a set of interferon-stimulated genes (ISGs) in peripheral blood has consistently been found in all reported patients with SAVI syndrome [6,14,15]. Modulation of IFN signature following treatment may represent a surrogate biomarker.…”
Section: Discussionmentioning
confidence: 99%